KEGIATAN KULIAH KERJA NYATA TEMATIK MAHASISWA DI DESA SUKAMAKMUR - Isnanto, Isnanto (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Improving clean and healthy living behaviour is very important to improve SDG’s of a healthy and prosperous village. Besides that, giving PHBS concepts to students at the elementary school level needs to be done early. The purpose of public service was to educate students of an elementary school in Sukamakmur Village, Tolangohula District, Gorontalo Province to improve PHBS and other activities during KKN Tematik activities. The program was done from 7th October to 23rd November 2022. The total number of students who followed in this activity was 78 from SDN 3 Tolangohula and 64 from SDN 6 Tolangohula. The method used in this activity was outreach to the community, especially students at SDN 3 and 6 Tolangohula. It can be concluded that the KKN Tematik program was well implemented and has been done some programs below: (1). Socialization of the PHBS program at SDN 3 involving 57 students and at SDN 6 Tolangohula involving 54 students, (2) Additional programs such as blood donation activities, sports activities, artistic and Fashion Show in the "Sukamakmur Festival" activities, and involved in religious activities with the community.